EXPERIENCE OF COUNTRIES IN COMBATING ILLEGAL TRAFFICKING OF DRUGS - MUSAEV, Djamaliddin (Тараққиёт тадқиқотлари: илмий-амалий анжуманлар материаллари тўплами, 2025)
At the beginning of the 21st century, countries of the world found themselves in the sphere of activity of transnational organized criminal organizations specializing in illegal drug trafficking. However, not all states are capable of resisting it. Modern anti-narcotics legislation abroad began to take shape only in the early 20th century. The first federal law in the United States regarding drug circulation, passed by Congress in 1914, prohibited the cultivation, possession, sale, and distribution of opiates and cocaine for non-medical purposes and provided for penalties for doctors (pharmacists) who dispensed these substances for non-medical use.